2017
DOI: 10.1128/aac.00073-17
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Assessment of Combined Polymyxin B and Minocycline Therapy against Klebsiella pneumoniae Carbapenemase (KPC)-Producing K. pneumoniae

Abstract: The multidrug resistance profiles of carbapenemase (KPC) producers have led to increased clinical polymyxin use. Combination therapy with polymyxins may improve treatment outcomes, but it is uncertain which combinations are most effective. Clinical successes with intravenous minocycline-based combination treatments have been reported for infections caused by carbapenemase-producing bacteria. The objective of this study was to evaluate the activity of polymyxin B and minocycline combination therapy against six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Repurposing veterinary medicines for human use has gained signif- icant interest recently, and several potential polymyxin combinations have been identified (40,41). To date, the majority of synergistic polymyxin combinations identified involve carbapenems, rifampin, and penicillin against P. aeruginosa, Acinetobacter baumannii, and Klebsiella pneumoniae, and a few studies reported synergetic combinations with fluoroquinolones against K. pneumoniae (24,25,28,29,31,42,43).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Repurposing veterinary medicines for human use has gained signif- icant interest recently, and several potential polymyxin combinations have been identified (40,41). To date, the majority of synergistic polymyxin combinations identified involve carbapenems, rifampin, and penicillin against P. aeruginosa, Acinetobacter baumannii, and Klebsiella pneumoniae, and a few studies reported synergetic combinations with fluoroquinolones against K. pneumoniae (24,25,28,29,31,42,43).…”
Section: Discussionmentioning
confidence: 99%
“…Two models have been proposed to explain the enhanced antibacterial activity achieved with the polymyxin combination therapy (24,(28)(29)(30)(31). Subpopulation synergy involves the killing of a subpopulation resistant to polymyxins by the second antibiotic and vice versa.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…colistin [29]. The combination of polymyxin B and minocycline also shown bactericidal efficacy against Klebsiella pneumoniae carbapenemase-producing K. pneumonia in a preliminary in vitro study [30].…”
Section: Bactericidal Activity In Vitro and In Vivomentioning
confidence: 95%